Literal Reading Comprehension Ability of English Study Program Students of Politeknik Negeri Jember - Agus Setia Budi; Cholimatus Zuhro (Journal of English in Academic and Professional Communication, 2023)
This article addresses the result of study that was carried out at the English Study Program, Politeknik Negeri Jember. This research was conducted to determine reading comprehension ability especially literal reading comprehension ability. The study is a descriptive quantitative research because it describes students' literal reading comprehension ability. In this study, data was used to describe and report students' ability in understanding literal text. In this study, researcher used a purposive sampling technique so that he made all students of the English Study Program in Semester1 for the 2020/2021 Academic Year as samples to be studied in this study. The samples taken in this study were 64 students who took reading course (literal reading course). To analyse the data in this study, the researcher conducted a literal reading test to measure their literal reading comprehension ability.